Karakteristik Masyarakat Dalam Penggunaan Moda Transportasi Kereta Api Dan Bus Madiun-Surabaya - Iswanto, Ary Putra; Wirawan, Willy Artha (Politeknik Perkeretaapian Indonesia Madiun, 2020)
The mode of transportation is one very important factor in accelerating the socioeconomic growth of a region. Surabaya is the capital of East Java Province and is one of the largest cities on the island of Java. The city of Surabaya which bears as the capital provides a variety of infrastructure facilities in an effort to serve the community, especially in the field of transportation. Some of the modes of transportation that are developing in this city are trains and buses with routes in several small cities in East Java. In this study the authors wanted to know the characteristics of the community in the use of rail and bus transportation modes from the direction of Madiun-Surabaya. This study uses a questionnaire instrument with sampling techniques Solvin, Issac Michael and Morgan, then data analysis using descriptive models. From the results of the study, it is known that the characteristics of the community based on the price attribute mostly use bus transportation, based on the attribute of the timeliness of choosing a train and based on the hadway and the frequency tends to be the same.